SCO and BRICS in an emerging multipolar world order - D. V. Malyshev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The year 2024 will be a milestone for the development of both the Shanghai Cooperation Organization (SCO) and BRICS, a unique negotiating format for rapidly growing economies. This year, Kazan will host the BRICS summit, and Astana has already held the SCO summit, which was marked by the adoption of a number of important initiatives. The assessment of the results and historical significance of these summits requires a special study, in this article we will look at the state in which both BRICS and SCO approached them, what problems they are currently facing and what prospects open up to them in the context of a global transformation of the IR system. The first section examines the main stages of the formation and current trends in the development of the SCO. The author emphasizes that in addition to addressing traditional challenges, the SCO member states are actively cooperating in countering new threats, such as separatism, drug trafficking, terrorism, and Islamic extremism. In this context, the SCO countries are particularly attentive to the rapidly changing situation in Afghanistan. The author concludes that although the SCO member countries have managed to create a solid legal framework and effective mechanisms of interaction, there are contradictions and even clashes between them on a number of issues. The second section identifies the stages of formation and current trends in the development of BRICS. The author notes that in the last few years, BRICS have been actively expanding both quantitatively by including more and more new countries in the association, and qualitatively, exploring new forms and areas of cooperation. In this regard, special attention is paid to the efforts to create a BRICS currency and to cooperation within the framework of the New Development Bank. According to the author, the SCO summits in Astana and BRICS in Kazan in 2024 should bring the development of these international structures, which embody hopes for the establishment of a new, fairer world order, to a qualitatively new level.